2018
DOI: 10.3390/en11071836
|View full text |Cite
|
Sign up to set email alerts
|

Utilising Unused Energy Resources for Sustainable Heating and Cooling System in Buildings: A Case Study of Geothermal Energy and Water Sources in a University

Abstract: Recently, Korea has become increasingly interested in unused, but possibly useful energy resources, due to the world-wide controversy over nuclear power and limitations in renewable energy production. Among these unused resources, the water that is produced in our surroundings is available as a potential energy source for heating, cooling and domestic hot water. This water is relatively stable on the supply side, available as a high-efficiency source in all seasons, and is continuously replenished without poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This reasoning seems to find support in the literature: several examples (see e.g. [54,55]) can be found illustrating how models of transient fluid transport inside the tubes would be justified only for much smaller time scales 4 . There are different ways to simplify the implementation of fluid flow, in order to reduce the computational time; for example, in [24,42] the convective heat transfer associated with the fluid flow was simulated by an equivalent solid with the same thermophysical properties of the actual circulation fluid.…”
Section: Brine Flow Modellingmentioning
confidence: 58%
See 2 more Smart Citations
“…This reasoning seems to find support in the literature: several examples (see e.g. [54,55]) can be found illustrating how models of transient fluid transport inside the tubes would be justified only for much smaller time scales 4 . There are different ways to simplify the implementation of fluid flow, in order to reduce the computational time; for example, in [24,42] the convective heat transfer associated with the fluid flow was simulated by an equivalent solid with the same thermophysical properties of the actual circulation fluid.…”
Section: Brine Flow Modellingmentioning
confidence: 58%
“…One can see that the difference is negligible, confirming our assumption at the beginning of this section that we can safely ignore the fluid flow. We accordingly model the U-pipes as made of concrete with constant T, 4 In particular, Ref. [54] shows that a steady-state, a transient and a semi transient model converge already after ∼ 3 hrs.…”
Section: Brine Flow Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review [2] on the utilization of geothermal energy [3,4] revealed that, by 2015, 49 countries invested over 20 billion USD in geothermal plants, which resulted in energy savings of ca 52.5 million tonnes of equivalent oil. This prevented respectively 46 and 148 million tonnes of carbon and CO 2 from being released into the atmosphere every year.…”
Section: Introductionmentioning
confidence: 99%
“…It is a passive technology that consumes low or no energy with almost no emissions as compared to conventional HVAC technologies, that is why it is termed as a green building technology [9]. EAHE consumes geothermal energy, which is renewable and hence sustainable source of heating and cooling in buildings [10]. EAHE reduces greenhouse gases emissions as it does not use any refrigerant as working fluid.…”
Section: Introductionmentioning
confidence: 99%